PSM UMPSA Staff Prepare Heartwarming Iftar Meal on 9 Ramadan 1446H - Muhammad Azrin, Ahmad (Pusat Sains Matematik (PSM), 2025)
In the spirit of Ramadan, on March 10, 2024 (9 Ramadan 1446H), PSM UMPSA staff came together to prepare an iftar meal for staff, students, and visitors at UMPSA Gambang Campus. The meal featured Ayam Masak Lemak Cili Api and Sayur Campur, fostering a sense of community during the holy month.